Degree of importance of finance and costs in the business sector - Paez Advincula, Rafael Roosell (2018)
The objectives of this research are to show the integrated financial and costs analysis that has gained importance in the business world, to evaluate financial performance and operative costs, to correct problems, and to apply corrective measures for company decision-making. A study carried out through an exhaustive review made it possible to expand upon cost and finance matters in the business sector, which has gained greater importance in investment analysis and decision-making models in the business sector, so that business leaders are able to identify the viability of their respective investments to improve profitability.